Divide and conquer, or the disintegration of strategic management: It's time to celebrate. (May 2016) - Arend, Richard J.
Every so often it is useful for a field of study to take the time to self-reflect and consider its existence from a high level in order to re-evaluate and possibly re-direct its resource allocations moving forward (where such reflection has become a wonderful and valuable standard in Strategic Organization! ). In this essay, we counter Hambrick's call to consolidate with a radical suggestion to separate the field of strategic organization into at least two camps. We offer a sound logic for that split and detail its hypothetical positive implications for the field in terms of the possibilities for improved research resource allocation and improved practical impact.